Modified Low-Dose Triiodo-L-thyronine Therapy Safely Improves Function Following Myocardial Ischemia-Reperfusion Injury - Rajagopalan, Viswanathan; Zhang, Youhua; Pol, Christine; Costello, Clifford; Seitter, Samantha; Lehto, Ann; Savinova, Olga V.; Chen, Yue-feng; Gerdes, A. Martin (Frontiers in Physiology, 2017)
Background: We have shown that thyroid hormones (THs) are cardioprotective and can be potentially used as safe therapeutic agents for diabetic cardiomyopathy and permanent infarction. However, no reliable, clinically translatable protocol exists for TH treatment of myocardial ischemia-reperfusion (IR) injury. We hypothesized that modified low-dose triiodo-L-thyronine (T3) therapy would confer safe therapeutic benefits against IR injury. Methods: Adult female rats underwent left coronary artery ligation for 60 minutes or sham surgeries. At 2 months following surgery and T3 treatment (described below), the rats were subjected to functional, morphological, and molecular examination. Results: Following surgery, the rats were treated with T3 (8 μg/kg/day) or vehicle in drinking water ad libitum following IR for 2 months. Oral T3 significantly improved left ventricular (LV) contractility, relaxation, and relaxation time constant, and decreased beta-myosin heavy chain gene expression. As it takes rats 6 hours post-surgery to begin drinking water, we then investigated whether modified T3 dosing initiated immediately upon reperfusion confers additional improvement. We injected an intraperitoneal bolus of T3 (12 μg/kg) upon reperfusion, along with low-dose oral T3 (4.5 μg/kg/day) in drinking water for 2 months. Continuous T3 therapy (bolus + low-dose oral) enhanced LV contractility compared with oral T3 alone. Relaxation parameters were also improved compared to vehicle. Importantly, these were accomplished without significant increases in hypertrophy, serum free T3 levels or blood pressure. Conclusions: This is the first study to provide a safe cardiac therapeutic window and optimized, clinically translatable treatment-monitoring protocol for myocardial IR using commercially available and inexpensive T3. Low-dose oral T3 therapy supplemented with bolus treatment initiated upon reperfusion is safer and more efficacious.